STUDI RESEPSI KHALAYAK DALAM AKUN YOUTUBE â€œJEDA NULISâ€ HABIB JAâ€™FAR HUSAIN TENTANG FENOMENA CITAYAM FASHION WEEK - Hidayat, Aufa Maulana; Murniati, Murniati (An-Nida : Jurnal Komunikasi Islam, 2024)
Citayam Fashion Week went viral in 2022, with the viral Citayam Fashion Week, many public figures came there. One of them is Habib Ja'far Husain. Habib Ja'far Husain is known as a millennial preacher, because he uses YouTube as a medium for preaching. With da'wah on YouTube, one of the audience's responses is through comments on YouTube. These comments or responses are considered important to be examined because to find out how effective Habib Ja'far Husain's da'wah was in using the media. This study aims to find out and analyze audience reception on Habib Ja'far Husain's "Jeda Nulis" youtube account about the Citayam Fashion Week phenomenon. The theory used in this study is the audience reception theory from Stuart Hall. The method used in this study is a qualitative descriptive research method carried out with the Stuart Hall audience reception analysis approach through three positions, namely the dominant position, the negotiating position, and the opposition position. The results of this study are the number of comments on the Jeda Wulis youtube account about the Citayam Fashion Week phenomenon, there are 741 comments. Of the 741 comments that occupied a dominant position, there were 448 comments and in the negotiating position, there were 293 comments. Of the 741 comments, none held an oppositional position. The researcher only took five comments based on the most likes as the data source to be analyzed. Of the five comments, it shows that most of the comments occupy a dominant position, indicating that these comments accept the contents of the content on the Paus Nulis YouTube account about the Citayam Fashion Week phenomenon that it consumes. However, two comments were also found that were in negotiating positions, indicating that the content on Jeda Nulis's YouTube account about Citayam Fashion Week was only partially accepted in the process of interpreting messages and comments in this position had criticism and personal opinions regarding the contents of the content they consumed.